Effect of Meat Type on the Compositional and Functional Characteristics of Meat Sauce During Refrigerated Storage for Shelf-Life Evaluation - Batool, Saira; Shaukat, Amal; Zahra, Syeda Muskan; Shahid, Komal; Khursheed, Saliha; Zahra, Andleeb; Athar, Rimza; Javed, Shanza; Fazal, Ayesha; Amjad, Kashaf; et al. (Biological and Clinical Sciences Research Journal, 2025)
Meat sauce is a very practical food that makes preparing wholesome meals quick and simple. It eliminates the need for intricate cooking procedures by combining premium protein with deep flavors. It improves the flavor and variety of pasta, rice, and other foods while saving time for time-pressed customers. It can be readily reheated or used immediately. It is the perfect choice for contemporary lifestyles due to its long shelf life and versatility. Objective: This study focuses on the development, physicochemical, and functional properties, and storage stability of meat sauces made from different types of meats. Methods: A laboratory-based experimental study was conducted from March to July 2025. Three treatment formulations were prepared: T1 (minced chicken), T2 (minced beef), and T3 (minced mutton). Meat sauces were formulated using a modified protocol from Prayitno et al. (2021). Analyses were conducted on 0, 15 and 30 days to measure variations in moisture content, ash levels, fat content, protein content, and color analysis by using a handheld spectrocolorimeter (Lovibond, LC-400) and the CIE L a*b* scale. To assess shelf life, bacterial and mold counts were regularly monitored throughout the storage period. Additionally, pH, water-holding capacity, emulsifying capacity, and antioxidant activity were also determined during the storage period. Sensory evaluations were carried out by a panel of judges using a 9-point hedonic scale to assess the meat sauce’s taste, aroma, texture, and overall acceptability. The data collected from these evaluations were analyzed using Statistix 8.1 software, with a statistical significance set at p < 0.05. Results: Over a 30-day refrigerated storage period, all meat sauce samples exhibited a progressive decrease in moisture and protein content, accompanied by corresponding increases in ash and fat concentrations, likely due to moisture loss and concentration effects. Among the formulations, the T3 sample containing minced mutton demonstrated the highest free fatty acid (FFA) content and pH values, suggesting a greater degree of lipid hydrolysis and microbial activity compared to the other variants. In contrast, the T1 sample prepared with minced chicken showed superior emulsifying and water-holding capacities, reflecting better functional protein properties that enhance texture and stability. Sensory evaluation revealed that while T1 was generally well-accepted by the panelists, T2 (minced beef) achieved the highest overall acceptability scores, indicating favorable flavor and appearance attributes. Conclusion: The study investigates the nutritional advantages, sustainability and ease of access to consumers of using meat sauce in a variety of dishes. The sauce offers a blend of nutrients when it is incorporated into different dishes. This creative strategy promotes economic stability by sourcing meat from local shops. In addition, it fulfils the consumer demand for fresh and organic convenience meals, making it a viable choice for health-conscious individuals.